National Survey of American Life Self-Administered Questionnaire (NSAL-SAQ), February 2001-June 2003 - Jackson, James S. (James Sidney) ([Verlag nicht ermittelbar], 2010)
The National Survey of American Life, 2001-2003 (NSAL) was followed up by a self-administered interview (NSAL SAQ) as a way to reduce respondent burden following the 2 1/2 hour NSAL survey. The SAQ includes additional questions about social, group, and individual characteristics: psychological resources (i.e., John Henryism), group and personal identity (racial awareness and identity), as well as ideology and racial relations (i.e., social dominance; stratification beliefs; egalitarianism; national pride; work ethic; authoritarian, interracial contact; and exposure to Black social contexts); political attitudes (i.e., Race-conscious Policy Index, Race-blind Policy Index, Non-Electoral Participation Index); care of elderly values; job and financial stressors; and wealth. Demographic variables include age, race, and sex.